2015
DOI: 10.18632/oncotarget.3051
|View full text |Cite
|
Sign up to set email alerts
|

The multiple cellular functions of the oncoprotein Golgi phosphoprotein 3

Abstract: The highly conserved Golgi phosphoprotein 3 (GOLPH3) protein, a component of Trans-Golgi Network (TGN), has been defined as a “first-in-class Golgi oncoprotein” and characterized as a Phosphatidylinositol 4-phosphate [PI(4)P] effector at the Golgi. GOLPH3 is commonly amplified in several solid tumors. Furthermore this protein has been associated with poor prognosis in many cancers. Highly conserved from yeast to humans, GOLPH3 provides an essential function in vesicle trafficking and Golgi structure. Recent da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 108 publications
(210 reference statements)
2
64
0
Order By: Relevance
“…In addition, GOLPH3 plays an important role in integrin-mediated cell migration via the up-regulation of sialylation [8], which suggests that GOLPH3 might regulate the progression of the tumors through its biological roles of glycosylation. Although it is generally accepted that the GOLPH3 has been implicated in retrograde trafficking of vesicles routed towards the Golgi [9], some studies reported that many receptors (e.g. transferrin receptor) recycle from perinuclear/trans Golgi region via recycling endosomes rather than getting into the constitutive secretory traffic [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GOLPH3 plays an important role in integrin-mediated cell migration via the up-regulation of sialylation [8], which suggests that GOLPH3 might regulate the progression of the tumors through its biological roles of glycosylation. Although it is generally accepted that the GOLPH3 has been implicated in retrograde trafficking of vesicles routed towards the Golgi [9], some studies reported that many receptors (e.g. transferrin receptor) recycle from perinuclear/trans Golgi region via recycling endosomes rather than getting into the constitutive secretory traffic [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…iii) Apart from GOLPH3, other proteins from the GOLPH family, such as GOLPH2, were identified to be ectopically expressed in GCs (27). iv) Even though a full underlying molecular mechanism was not observed, GOLPH3 was proven to play an essential role in vesicle trafficking and Golgi structure (28). Moreover, Field et al found that overexpression of GOLPH3 confers resistance to killing by DNA-damaging agents and depletion of GOLPH3 could enhance the ability of DNA-damaging agents to kill cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…The oncogenic activity of GOLPH3 has been primarily correlated with its ability to influence signaling downstream of the mammalian target of rapamycin (mTOR), resulting in enhanced activation of both mammalian TORC1 and TORC2 complexes [9,10]. This idea was supported by preclinical treatment studies showing that GOLPH3-expressing tumors are much more sensitive to mTOR inhibitors, raising the possibility that GOLPH3 levels might predict rapamycin efficacy in tumor therapy.…”
Section: The Pi(4)p Binding Protein Golph3 Is An Oncoproteinmentioning
confidence: 99%